Simulation of the EDC Purification Unit of a MVC Plant - López, Yadira; Sánchez, Jorge; Hernández, José; Leal, Ingrid (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Simulation models, by means of the commercial program Aspen Plus, were built for the different columns that integrate the purification unit of 1,2 dichloroethane (EDC) of a vinyl chloride plant. These models can be used to evaluate and/or to predict the system behaviour for helping to take corrective actions and/or to define operation strategies. The thermodynamic method NRTL-RK were validated well the design data for light component and vacuum distillation columns, and the state equation of Lee-Keesler-Plocker for the heavy component column. The simulation models properly fit the data of the columns under operation conditions. Sensitivity analyses were carried out to evaluate the light component content in the bottom product of the light component column, varying the feed load into the column, the amount of the light components and the heat needed to maintain the concentration of those components at the required specifications. A higher effect occurs on the light component content in the bottom product of this column as the feed load increases over 30000 kg/h. The presence of light components in the feed (carbon tetrachloride, chloroform, etc.) in higher amounts than the design values did not affect the composition of the bottom product of the column. The hydraulic study demonstrated that all the columns have flexibility to operate with feed loads higher than the design feed loads